Gaya Kepemimpinan Kepala Sekolah dalam Membentuk Karakter Sumber Daya Manusia (Human Resources) di Lingkungan Sekolah - Wahyu Tri Wijayati (DIDAKTIKA, 2024)
The management of a school is greatly influenced by the leadership style of a school principal. The aim of this research is to identify the application of good practices and strategies applied by school principals to build human resources in the UPT SD Negeri 229 Gresik school environment with character. The research method used in this research is a qualitative research method, where the informants for this research include the principal, teachers, students and guardians of UPT SD Negeri 229 Gresik. The research results show that the leadership style used by the principal of UPT SD Negeri 229 Gresik always appreciates every new breakthrough idea, innovation and even ideas from teachers and staff of UPT SD Negeri 229 Gresik and always applies a culture of discussion at every event and in almost all programs and policies. to be taken. In building student character at the school, the principal of UPT SD Negeri 229 Gresik also implemented several programs to improve vital aspects of behavior including religion, tolerance, discipline, responsibility and cooperation. The results of interviews conducted with teachers and staff, as well as students and several parents of UPT SD Negeri 229 Gresik, the principal was able to apply values, especially the application of disciplinary character both among teachers and students, strengthening religious values. Behavioral changes related to the character of teachers and students in a positive direction have been very clearly observed since the leadership of the new school principal.